Acute Clinical Manifestation of Mesenteric Heterotopic Pancreatitis: A Pre- and Postoperative Confirmed Case - Bente M. de Kok; Fleur I. de Korte; Lars E. Perk; Valeska Terpstra; J. Sven D. Mieog; Frank M. Zijta (Case Reports in Gastrointestinal Medicine)
Heterotopic pancreas is a relatively uncommon congenital anomaly, defined as pancreatic tissue in ectopic sites without an anatomic and vascular continuity with the main body of the pancreas. We report the case of a 58-year-old woman who was admitted to the hospital with the clinical suspicion of a mild, acute pancreatitis. Computed tomography, magnetic resonance imaging, transabdominal ultrasound, and endoscopic ultrasound revealed a normal orthotopic pancreas and the suspicion of a large heterotopic pancreas in the small bowel mesentery with signs of acute inflammation. The diagnosis of mesenteric heterotopic pancreatitis was preoperatively confirmed by endoscopic ultrasound-guided fine-needle aspiration and consequently histologically established after surgical resection.